Literature Study on MurÄbaá¸¥ah Financing in Islamic Banking in Indonesia - Maulidizen, Ahmad (Economica: Jurnal Ekonomi Islam, 2018)
Islamic banking in Indonesia has experienced significant growth, including assets, financing provided and the number of customers. Islamic bank financing 70-80% is given to the community by using the contract of mur?ba?ah, in the form of consumptive and productive. Islamic bank operations must be guided by Fatwa of the National Sharia Council in order to carry out its optimal function economically and to run the Shari'a comprehensively. Therefore, this article will explain the concept of mur?ba?ah conceptually and application in Islamic banking in Indonesia. The purpose of writing this article so that the implementation of Mur?ba?ah contract in Islamic Bank in Indonesia can be in accordance with the principles of Shari'a that put forward the principle of justice and no party is harmed.Perbankan syariah di Indonesia telah mengalami pertumbuhan yang signifikan, termasuk aset, pembiayaan yang diberikan dan jumlah pelanggan. Pembiayaan bank syariah 70-80% diberikan kepada masyarakat dengan menggunakan kontrak mur?ba?ah, dalam bentuk konsumtif dan produktif. Kegiatan bank syariah harus dipandu oleh Fatwa Dewan Syariah Nasional untuk menjalankan fungsi optimalnya secara ekonomis dan menjalankan syariat secara komprehensif. Oleh karena itu, artikel ini akan menjelaskan tentang konsep mur?ba?ah secara konseptual dan aplikasinya pada Bank Islam di Indonesia. Tujuan penulisan artikel ini agar pelaksanaan kontrak Mur?ba?ah di Bank Syariah di Indonesia dapat sesuai dengan prinsip syariah yang mengedepankan asas keadilan dan tidak ada pihak yang dirugikan.